PENGGUNAAN BAP DAN TDZ UNTUK PERBANYAKAN TANAMAN GAHARU (Aquilaria malaccensis Lamk.) (The Use of BAP and TDZ for Propagation of Agarwood (Aquilaria malaccensis Lamk.)) - . Azwin; Iskandar Z. Siregar; . Supriyanto (Department of Forest Resources Conservation and Ecotourism - IPB University, 2006)
Agarwood (A. malaccensis Lamk.) is one of the important tropical forest trees, which produces a high economically valuable fragrant resinous wood. The increase of agarwood demand from year to year leads to uncontrolled illegal harvest of this plant from its natural habitat. To encounter this problem, there is an urgent need to develop agarwood plantation. Tissue culture is an alternative method to provide genetically good seedlings for plantation in the future due to its short period and mass quantity of planlet production. In addition, through this method, its might also provide homogenous plant, and free pest and diseases. The objectives of the study were (1) to find out the optimal concentration of BAP or TDZ for inducing shoot multiplication of agarwood in in vitro conditions. MS (Murashige And Skoog, 1962), was used as basal media. The experimental design of the research was completely randomized design (RAL) with treatment of BAP concentration (control; 0,50 ppm; 0,75 ppm; 1,0 ppm) or TDZ concentration (control; 0,25 ppm; 0,50 ppm; 0,75 ppm), in 3 units, of replicate every units consist of 4 bottles, every bottle containing one explants coming from axillaries and adventitious shoot explants. Results indicated that two types of agarwood explants grown in vitro in MS basal media containing BAP 0,50 ppm or TDZ 0,25 ppm produced the highest number of shoots and leaves of agarwood plantlets, as well as its plantlet shoot length.Keywords : BAP , TDZ , Agarwood, In Vitro.